Les Tables d’orientation du Touring Club de France (1903-1960) : pratique et connaissance du paysage par les images - Rachel Floch (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Orientation tables are small touristic structures that represent a painted and mapped landscape on circular enamelled lava platforms. Built on heights since the end of the 19th century, they are part of a practice of walking as « tours » where the territory is reduced and materialized from a unified point of view. If these objects are inserted, like key points, in situ in a territory, they act, simultaneously, in visu, by producing a landscape representation within the duration of the walk. Considering these objects as « image-buildings », we analyze them through the prism of photomontage to show to what extent they accompany a mediation process, using images to guide the experience of a landscape. The orientation tables are a form of graphic montage, which allows us to conceive landscape as a space that is measured by the body in movement, which also becomes a space for sharing an experience, both real and virtual, between a search for amplitude and an attempt to go beyond the limits of the visible.